Drivers of foreign direct investment in the EU: Regulatory distance and revealed technological advantage - Chiara Castelli; Ronald B. Davies; Mahdi Ghodsi; Javier Flórez Mendoza (University College Dublin, UCD School of Economics, 2025)
This study examines the interplay between trade policy, in particular non-tariff measures (NTMs), and revealed technological comparative advantage (RTA) at the NUTS2 level as drivers of foreign direct investment (FDI) over time. Combining data from the Orbis database (Bureau Van Dijk), the NTMs database (WTO I-TIP) and the European Patent Office (EPO PATStat), we construct a comprehensive panel database of European firms owned by foreign EU and non-EU firms. This database includes financial information for both parent companies and subsidiaries, as well as detailed country and sector-specific trade barriers from the perspective of both the home and host economies. Furthermore, this database allows us to compute tailored RTA variables reflecting firm-specific technological interests proxied by firms' patent production across technology classes. Using a Poisson Pseudo Maximum Likelihood (PPML) estimator, our analysis reveals a heterogeneous impact of NTMs and RTAs on FDI investment in the EU regions. Specifically, while increasing regulatory distance Technical Barriers to Trade (TBT) and Sanitary and Phytosanitary Standards (SPS) measures hampers FDI investment from extra-EU companies, the results on tariffs support the regulatory jumping motive. Furthermore, local technological capabilities significantly support FDI, especially when RTAs reflect the technological interests of the foreign-owned subsidiary, while the effect is reversed when accounting for the innovation portfolio of the parent company.
Keywords: F23; O24; O34; R58; 330; FDI; tariff and non-tariff measures; revealed technological advantage